Seismic fragility analysis of the inter-story isolated structure for the influence of main-aftershock sequences. (January 2023) - Yang, Fan; Liu, Dewen; Lei, Min; Zheng, Yanping; Zhao, Tiange; Gao, Liang
The inter-story isolated structure is an effective and feasible structure seismic technology and system, but most studies on inter-story isolated structures only consider the mainshock. A strong mainshock is usually accompanied by multiple aftershocks, the structure will be damaged under the action of the mainshock. Because of the short time interval between the main shock and the aftershocks, the structure is often not repaired in time, so it will be further damaged under the action of the aftershock. Therefore, it is meaningful to study the fragility of inter-story isolated structures under the action of main-aftershock sequences. In this study, the incremental dynamic analysis method was used, and the inter-story isolated structure of a frame shear wall was established. The vulnerability curves of each substructure under the action of a single mainshock and main-aftershock sequence were compared. A series structure system was used to calculate the overall vulnerability of the inter-story isolated structure. The vulnerability curves of different isolation layer setting positions and isolation bearing stiffness under the action of a single mainshock and main-aftershock were compared, and the collapse margin ratio (CMR) of the structure given. The results show that aftershocks increase the exceedance probability of each substructure, and with an increase in the limit state, the influence of aftershocks is more obvious. An appropriate isolation layer design reduces the influence of aftershocks and the exceedance probability of the entire structure.